THE UNTRANSLATABILITY OF JOKES IN TREVOR NOAH’S SON OF PATRICIA - Gulo, Ingatan; Prakoso, Dimas Bimo (Linguistics and Literature Journal, 2025)
This study investigates cases of untranslatability and the translation strategies applied in Trevor Noah’s stand-up comedy special Son of Patricia. Employing a qualitative research approach, the study analyzes jokes that are considered difficult to translate directly from English into Indonesian. The classification of untranslatability is based on Peter Newmark’s theory, while the translation strategies are examined using Vinay and Darbelnet’s framework. The analysis focuses on identifying lexical and cultural untranslatability present in the selected data. The findings reveal that untranslatability should not be viewed as a constraint in translation but rather as an opportunity for translators to exercise creativity and problem-solving skills. Many jokes that pose translation challenges can be effectively rendered by selecting the most appropriate equivalents in the target language through the use of suitable translation strategies. The strategies most frequently employed include modulation, equivalence, adaptation, and borrowing. All of these play a crucial role in preserving the humorous effect and the intended meaning of the source text. This study emphasizes the importance of cultural awareness and strategic competence in translating humor, particularly in entertainment texts rich in linguistic and cultural nuances. The research contributes to the field of applied linguistics and translation studies by demonstrating that appropriate translation strategies can bridge language and cultural gaps while maintaining the quality and impact of the original content.Keywords: stand-up comedy, translation strategies,  untranslatability